The Integration of Eco-Literacy in Teaching-Learning Activities as An Effort to Reduce Environmental Crisis - Amalia, Dini (MADINAH, 2024)
This study explores the integration of eco-literacy values within the framework of teaching and learning activities, aligning with the principles of Islamic thought. Recognizing the growing importance of environmental awareness and sustainability in today’s world, this study delves into the potential synergies between Islamic values and ecological consciousness. It employs a qualitative research design, incorporating literature reviews from both Islamic principles and environmental studies. Through this multidimensional approach, the research seeks to identify the integration of eco-literacy values into diverse subjects across teaching-learning activities within an Islamic educational framework. The study also investigates the challenges and opportunities associated with implementing such an approach in educational settings, considering cultural contexts and varying levels of environmental awareness. By promoting a comprehensive understanding of ecological principles rooted in Islamic thought, this study envisions contributing to the development of environmentally conscious, responsible, and ethical individuals who integrate Islamic values into their daily lives, fostering a harmonious relationship between humanity and the natural world. Keywords: Eco-Literacy, Teaching-Learning Activities, Islamic Thought.